Ironi Dan Humor Konten Youtube “Lapor Pak!” Dalam Perspektif Tindak Tutur - Nurul Iqlimah Faradiba; Abd. Rahman Rahim; Wahyu Ningsih (Pusat Riset dan Inovasi Nasional, 2025)
Overall, the primary aim of this study is to explain the types of irony and humor found in the YouTube content Lapor Pak! using the perspective of speech act theory. Specifically, the research seeks to identify the types of locutionary, illocutionary, and perlocutionary acts that form ironic and humorous utterances. This study also aims to contribute to the understanding of pragmatics, particularly within the context of digital communication. This research employs a qualitative approach using descriptive methods. The data source consists of utterance transcripts from several episodes of Lapor Pak! as aired on the Trans7 YouTube channel. Data collection techniques include observation, documentation, and noting utterances that contain elements of humor and irony. The collected data is then analyzed based on speech act theory to determine how irony and humor are constructed in the conversation. The results show that out of 20 utterances analyzed, 19 contained humorous elements and 5 contained irony, with some utterances featuring both simultaneously. The most dominant types found were verbal humor and verbal irony. From the perspective of speech acts, expressive acts were the most frequently used to construct both irony and humor, followed by representative and directive acts. This study concludes that the utterances in Lapor Pak! often use humor as a medium to convey messages through an expressive approach. Humor is not only intended to entertain but also functions as a subtle means of delivering social criticism, making the message more acceptable to the audience. Thus, this study highlights that speech acts in digital contexts like YouTube can serve as both effective and entertaining forms of communication.